Development of a Wearable Patch Antenna for Patient Monitoring - Yusuf Wada, Muhammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
This research sees to developing a miniature/wearable microstrip patch antenna which will be lightweight and have a reasonable flexibility limit. Within this study thus, microstrip patch antenna (MSA) using CST studio was sized and designed. In this regard, this research sees to developing a miniature/wearable microstrip patch antenna for patient monitoring applications. The features of the antenna are specifically chosen to ensure that it meets up with the requirement of the patch antenna. This is to ensure its compact size, effective length and good transmissions which are all pre-requisite for a patch antenna intended for patient monitoring purpose as it’s designed to be worn on the body. The study comprises of an introductory chapter which gives a general information on the study background, problem statement, justification of study, scope of research, aim and objectives, advantages and disadvantages and the thesis guide. The chapter two encapsulates the review of literature, the third chapter covers the methodology and procedure for the simulation of antenna, the chapter four introduces the results and discussion of the simulation and chapter five concludes the research with recommendations.

ÖZ: Bu araştırma, hafif olacak ve makul bir esneklik sınırına sahip olacak minyatür / giyilebilir bir mikroşerit yama anteni geliştirmeyi amaçlamaktadır. Bu çalışmada, CST studio kullanılarak mikroşerit yama anteni (MSA) boyutlandırıldı ve tasarlandı. Bu bağlamda, bu araştırma hasta izleme uygulamaları için minyatür / giyilebilir bir mikroşerit yama anteni geliştirmeyi amaçlamaktadır. Antenin özellikleri, yama anteninin gereksinimini karşıladığından emin olmak için özel olarak seçilmiştir. Bu, vücuda giyilmek üzere tasarlandığı için hasta izleme amacına yönelik bir yama anteni için ön koşul olan kompakt boyutunu, etkili uzunluğunu ve iyi iletimlerini sağlamaktır. Çalışma, çalışmanın geçmişi, sorun açıklaması, çalışmanın gerekçesi, araştırmanın kapsamı, amaç ve hedefleri, avantaj ve dezavantajları ve tez rehberi hakkında genel bilgi veren bir giriş bölümünden oluşmaktadır. İkinci bölüm literatürün gözden geçirilmesini kapsıyor, üçüncü bölüm antenin simülasyonu için metodoloji ve prosedürü kapsıyor, dördüncü bölüm simülasyonun sonuçlarını ve tartışmasını tanıtıyor ve beşinci bölüm araştırmayı önerilerle sonuçlandırıyor.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2023. Supervisor: Prof. Dr. Şener Uysal.
Keywords: Thesis Tez; Electrical and Electronic Engineering; Wearable Patch Antennas--Patient Monitoring--Design and Construction; Telemedicine; Biomedical; Patient Monitoring; Microstrip Patch Antenna; Simulation; CST Studio